The Condition of Subjective Daytime Sleepiness and Its Related Decline in Work Productivity Among Daytime Workers - Yuta Takano; Toshiyuki Hirasawa; Yuichi Inoue (Journal of Epidemiology)
Background: Few have examined the condition of subjective daytime sleepiness in workers and its relation to their work productivity. This study aimed to clarify the association between the presence of subjective daytime sleepiness and work productivity measures, including presenteeism and absenteeism, as well as factors related to the presence of the symptom in daytime workers. Methods: This cross-sectional study included 17,963 daytime workers who attended the annual medical check-up. They were categorized into four groups; the daytime sleepiness group was defined as having only subjective daytime sleepiness, the insomnia group as having only insomnia symptoms, the combination group as having both subjective daytime sleepiness and insomnia symptoms, and the healthy group as having no sleep complaints. This study used demographics, health status, workplace, work productivity, and sleep items included in the self-reported medical check-up questionnaire. Results: The combination group had significantly worse presenteeism than other groups. The daytime sleepiness and insomnia groups had significantly worse presenteeism than the healthy group. The results of absenteeism were the same as presenteeism. Factors related to the positivity for subjective daytime sleepiness were presence of psychiatric disease, the positivity for habitual snoring and/or witnessed apnea, shorter sleep duration on workdays, long working hours, female sex, living alone, the amount of social jetlag, and younger age. Conclusion: Subjective daytime sleepiness, not just insomnia symptoms, has a significant negative impact on work productivity, and both workplace and individual approaches should not be ignored for addressing subjective daytime sleepiness among daytime workers.